Shepherds abiding eaudiobook - Karon, Jan (Mitford,, 2002)
The Mitford series has moved the hearts of millions of fans. Shepherds Abiding, which is accompanied here by two additional short stories, is a wonderful Christmas gift for all listeners. When Father Tim finds a battered nativity scene in an antique shop, he embarks on a humble endeavor to save it.